Implementation of Appsheet-Based Queue Management at Public Electric Vehicle Charging Stations SPKLU - Muhammad Ridhan Fadli Rahman; Dian Permata Sari (P3M Politeknik Negeri Bengkalis, 2025)
A significant increase in electric adoption in Indonesia has created high demand at public electric vehicle charging stations (SPKLU). Reliance on manual queue management methods at these stations often results in vehicular congestion and unstructured recording processes. This study implements and evaluates